2022
DOI: 10.3390/nano12101749
|View full text |Cite
|
Sign up to set email alerts
|

3D Polymer-Based 1 × 4 MMI Splitter

Abstract: Due to the increasing trend of photonic device miniaturisation, there is also an increased need for optical splitting in a small volume. We propose a smart solution to split light in three dimensions (3D). A 3D optical splitter based on multimode interference (MMI) for the wavelength of 1550 nm is here designed, simulated, fabricated and optimised for splitting at 1550 nm. We focus also on the possibility of its direct integration on an optical fibre. The design is focused on the use of 3D laser lithography ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The measured distributions in Figures 8 and 9 closely resemble the distributions acquired by the simulations. Further details about the fabrication and NSOM measurements of the 1 × 4 MMI splitter are available in our previous work [33]. Characterisation of the modal distribution across the output part was carried out using a highly resolved near-field scanning optical microscope (NSOM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured distributions in Figures 8 and 9 closely resemble the distributions acquired by the simulations. Further details about the fabrication and NSOM measurements of the 1 × 4 MMI splitter are available in our previous work [33]. Characterisation of the modal distribution across the output part was carried out using a highly resolved near-field scanning optical microscope (NSOM).…”
Section: Resultsmentioning
confidence: 99%
“…The measured distributions in Figures 8 and 9 closely resemble the distributions acquired by the simulations. Further details about the fabrication and NSOM measurements of the 1 × 4 MMI splitter are available in our previous work [33].…”
Section: Resultsmentioning
confidence: 99%
“…The 3D multimode interference splitting was firstly introduced in 3D 1x4 MMI splitter 4 . MMI splitters work on the principle of multiple reflections and interference in the multimode waveguide part.…”
Section: Design and Fabrication Of 3d Splittersmentioning
confidence: 99%
“…Although the planar MMI splitter technologies, especially on silicon platform are well published, the first 3D configuration was published only very recently 4 . MMI splitters has got to the forefront because of their attractiveness in photonic integrated circuits because of their small volume integration.…”
Section: Introductionmentioning
confidence: 99%
“…Its straightforward design and enhanced stability make it a compelling option for various optical uses, from telecommunications to sensing and signal processing. Many studies have shown that Y-branch MMI splitters work well in various applications [15][16][17][18][19][20]. They're good at splitting signals, don't lose much signal, and are easy to make.…”
Section: Introductionmentioning
confidence: 99%